Keefektifan Media Pembelajaran Pementasan Drama Berbasis Syair Perang Menteng Menggunakan Macromedia Flash (Effectiveness of Learning Media for Drama Performances Based on Syair Perang Menteng Using Macromedia Flash) - Ayu Agustina; Nurhayati Nurhayati; Didi Suhendi; Machdalena Vianty (Indonesian Language Education and Literature, 2022)
The purpose of this study was to examine the effectiveness of the use of Macromedia Flash media in the material for drama performances based on the Menteng War Poem. The research method used is a quasi-experimental research design with one group pretest and posttest. Data collection techniques using tests. The data analysis technique used a normality test followed by one sample t-test. The sample of this research is the third-semester students of S1 Indonesian Language & Literature Education Faculty of Teacher Training and Education, Sriwijaya University, totaling 28 people. From the results of hypothesis testing, the t-count value is 64.073 at df 27 with a significant level of 5%, and t table is 1.703. It was concluded that there was a significant effect on student learning outcomes in the play based on the Syair Perang Menteng using Macromedia Flash.Tujuan penelitian ini untuk menguji keefektifan penggunaan media Macromedia Flash pada materi pementasan drama berbasis Syair Perang Menteng. Metode penelitian yang digunakan adalah eksperimen semu dengan desain penelitian one group pretest posttest. Teknik pengumpulan data menggunakan tes. Teknik analisis data menggunakan uji normalitas dilanjutkan dengan uji one sample t-test. Sampel penelitian ini adalah mahasiswa semester tiga S1 Pendidikan Bahasa dan Sastra Indonesia Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwijaya yang berjumlah 28 orang. Dari hasil pengujian hipotesis diperoleh nilai t-hitung sebesar 64,073 pada df 27 dengan taraf signifikan 5% t tabel 1,703. Artinya, terdapat pengaruh yang signifikan terhadap hasil belajar mahasiswa pada pementasan drama berbasis Syair Perang Menteng menggunakan Macromedia Flash.